Carbon dioxide fixation and biomass production from combustion flue gas using energy microalgae. (September 2015) - Zhao, Bingtao; Su, Yaxin; Zhang, Yixin; Cui, Guomin
Abstract: Algae-based bioenergy has been regarded as the next generation of renewable energy. To fix CO2 from flue gas and harvest algal biomass for energy conversion, three energy microalgae, Chlorella sp., Isochrysis sp. and Amphidinium carterae, were investigated in 1-L bubble column photobioreactors with an aeration of 15% CO2 at the flue-gas level. According to the potential on CO2 fixation and biomass production, Chlorella sp. was selected as the dominant species due to its superiority to the other species, with a specific growth rate of 0.328 d −1, a biomass production rate of 0.192 gL −1 d −1 and a CO2 fixation rate of 0.353 gL −1 d −1 . Furthermore, Chlorella sp. was cultured under varied physicochemical parameters, including CO2 concentrations, aeration rates and toxic compounds (SO2, NO and Hg 2+ ) to assess its performances. The maximum specific growth rate, biomass production rate and CO2 fixation rate were found to be 0.372 d −1, 0.268 gL −1 d −1 and 0.492 gL −1 d −1 at a CO2 concentration of 10%; 0.375 d −1, 0.274 gL −1 d −1 and 0.503 gL −1 d −1 at an aeration rate of 0.1 vvm; and 0.328 d −1, 0.192 gL −1 d −1 and 0.353 gL −1 d −1 in the absence of toxic compounds, respectively. The results provide a basis for microalgal-based CO2 emission reduction and bioenergy utilization in pilot-scale applications. Graphical abstract: Highlights: CO2 fixation and biomass production from flue gas using three energy microalgae. Chlorella sp. was selected as the dominant specie due to superior performance. Effect of the key physicochemical parameters of flue gas was addressed. Potential of industrial application was analyzed. The results may provide a basis for microalgae-based energy utilization.